Vaccinations and Immune Response in Celiac Disease - Stefano Passanisi; Valeria Dipasquale; Claudio Romano (Vaccines, 2020)
Immune response to vaccinations in celiac patients is of growing scientific interest. However, some aspects of the relationship between celiac disease (CD) and vaccines are still unclear. A comprehensive search of published literature using the PubMed database was carried out using the following key terms: “adaptive immunity”, “celiac disease”, “humoral immune response”, “immunization”, and “vaccination”. To date, there is no evidence showing any causative association between vaccines and CD development. Therefore, vaccinations may be administered according to the modalities and timing of the National Immunization Schedule for each country. The rotavirus vaccine is currently recommended for the general population, and according to some data, it appears to reduce the risk for the development of CD autoimmunity in the early years of life. Regarding the hepatitis B virus, a booster dose of the vaccine is often required due to the low or the lost immune response rate in CD. Furthermore, determination of hepatitis B antibody titers could be useful in newly diagnosed CD subjects regardless of age at diagnosis. Finally, pneumococcal vaccines may be administered in patients with advancing age at diagnosis and concomitant risk factors. Future clinical practice guidelines for vaccination and monitoring programs in celiac patients could be recommended.